Influence of the pulmonary annulus diameter on pulmonary regurgitation and right ventricular pressure load after repair of tetralogy of Fallot. Issue 5 (1st November 2002) - Uebing, A; Fischer, G; Bethge, M; Scheewe, J; Schmiel, F; Stieh, J; Brossmann, J; Kramer, H H
Abstract : Objective: To assess the influence of the pulmonary annulus diameter after reconstruction of the right ventricular (RV) outflow tract at repair of tetralogy of Fallot on pulmonary regurgitation and RV pressure load; and to evaluate the impact of pulmonary regurgitation on RV size and function. Setting: Paediatric cardiology and diagnostic radiology departments of a tertiary referral centre. Patients: 67 patients were examined at a median of 4.8 years after repair of tetralogy of Fallot by means of biplane angiocardiography and magnetic resonance imaging (MRI). Main outcome measures: Pulmonary annulus diameter and area, pulmonary regurgitant fraction, RV to left ventricular (LV) systolic pressure ratio, RV end diastolic volume, and RV ejection fraction were assessed. Results: There was a significant positive correlation between pulmonary annulus area indexed to body surface area and pulmonary regurgitation (angiocardiography: r = 0.55, p < 0.001; MRI: r = 0.59, p < 0.001). No significant correlation was found between pulmonary annulus index and RV to LV systolic pressure ratio even in patients with small pulmonary annulus areas ( r = −0.24, NS). Pulmonary regurgitant fraction was positively correlated with normalised RV end diastolic volume (angiocardiography: r = 0.42, p < 0.05; MRI: r = 0.56, p < 0.01). RV ejection fraction decreased with increasing pulmonary regurgitation (angiocardiography: r = −0.42, p < 0.05; MRI: r = −0.41, p < 0.05). Conclusions: The extent of pulmonary regurgitation after tetralogy of Fallot repair correlates with the postoperative size of the pulmonary annulus and is closely correlated with the enlargement of the RV. An enlargement of the pulmonary annulus to the second lower standard deviation of normal results in a decrease of pulmonary regurgitation and is sufficient to achieve adequate RV pressure unloading.